2021
DOI: 10.1038/s41420-021-00646-2
|View full text |Cite
|
Sign up to set email alerts
|

A costimulatory molecule-related signature in regard to evaluation of prognosis and immune features for clear cell renal cell carcinoma

Abstract: Costimulatory molecules have been proven to enhance antitumor immune responses, but their roles in clear cell renal cell carcinoma (ccRCC) remain unexplored. In this study, we aimed to explore the gene expression profiles of costimulatory molecule genes in ccRCC and construct a prognostic signature to improve treatment decision-making and clinical outcomes. We performed the first comprehensive analysis of costimulatory molecules in patients with ccRCC and identified 13 costimulatory molecule genes with prognos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…A recent study identified a high‐risk model to predict prognosis in LUAD patients based on costimulatory molecule signature genes from the cancer genome atlas (TCGA) and Gene Expression Omnibus profiles 12 . In addition, a prognosis‐related signature was developed for clear cell renal cell carcinoma, which included 13 costimulatory molecular genes from the TCGA database 9 . However, these studies only focused on costimulatory molecular genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study identified a high‐risk model to predict prognosis in LUAD patients based on costimulatory molecule signature genes from the cancer genome atlas (TCGA) and Gene Expression Omnibus profiles 12 . In addition, a prognosis‐related signature was developed for clear cell renal cell carcinoma, which included 13 costimulatory molecular genes from the TCGA database 9 . However, these studies only focused on costimulatory molecular genes.…”
Section: Introductionmentioning
confidence: 99%
“…Killer T cells are activated after the creation of a signal if a major histocompatibility complex on antigen‐presenting cell is distinguished by T cell receptors, followed by dispensing some costimulatory molecules to a second signal. 9 Costimulatory molecules are crucial in the activation of T cells. 10 The costimulatory molecules family consists of 61 cell‐surface molecules that regulate the T cell activation and tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…There were no significantly differences in clinical characteristics between two sets (Table 1 ). Furthermore, a total of sixty costimulatory molecules genes (CMGs) were collected from prior reviews [ 21 , 22 ].…”
Section: Methodsmentioning
confidence: 99%
“…In order to evaluate the prognostic role of GPX4 in DLBCL, we used R 4.2.1 to conduct Lasso Cox regional analysis on GSE10846 and GSE181063 to obtain GPX4 prognostic risk model data, and conducted univariate analysis [27]. Then the prognosis of DLBCL patients after treatment was evaluated by analyzing the high and low expression of GPX4 with KM curve, and then veri ed in TCGA dataset to evaluate the potential ability of GPX4 as a prognostic marker of DLBCL.…”
Section: Prognostic Analysis Of Gpx4 In Dlbclmentioning
confidence: 99%